Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 5 Polynomials and Polynomial Functions - 5.7 Apply the Fundamental Theorem of Algebra - 5.7 Exercises - Problem Solving - Page 386: 63



Work Step by Step

Here, we have $2.724 \times 10^{-7} x^4-3.269 \times 10^{-5} x^3+9.806 \times 10^{-4} x^2=0$ Re-arrange as: $2.724 x^4-326.9x^3+9806 x^2=0$ or, $x^2(2.724 x^2-326.9x+9806)=0$ Now, $2.724 x^2-326.9x+9806=0$ $x=\dfrac{-(-326.9)\pm \sqrt {(326.9)^2-(4)(2.724)(9806)}}{(2)(2.724)}=59.24, 60.77$ Hence, $x=0,60$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.